“I feel so small and big at the same time”—exploring body experience and binge eating disorder following inpatient treatment: a qualitative study - Olsen, Helene T.; Vangen, Sunniva B.; Stänicke, Line Indrevoll; Vrabel, KariAnne (Frontiers in Psychology, 2024)
Background Limited research into binge eating disorder (BED), a low treatment rate, and a lack of treatment rights, reflects a marginalized disorder in society and a treatment context. Aim The aim of this study was to gain a deeper understanding of the psychopathology of BED, by exploring the patients’ meanings related to the disorder and the role of the body in the treatment of BED. Method Qualitative methodology using a reflexive thematic analysis. The data material is based on semi-structured in-depth interviews with six cis-gendered women who had previously completed an inpatient treatment program for BED at a department for EDs and met the criteria for 307.51 Binge Eating Disorder in DSM-5. Results The qualitative analysis rendered two meta-themes comprising six themes and 12 subthemes. The initial meta-theme was “Relational challenges and feelings could not be talked about at home.” The secondary meta-theme was “Body contempt disturbs the experience of self and others” and the third was “Their body has not been a theme in previous treatment.” This categorization depicts a narrative of the disorder in terms of development, current condition, and experiences with prior treatment. Discussion The findings indicate that shame and disgust are central to playing pivotal roles in the embodiment of BED, highlighting the significance of addressing one’s relationship with their body for achieving recovery and preventing an experienced repetition of the perceived rejection as a child.